(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
On the data on 110 lakes of Karelia the role of natural and anthropogenic factors in the forming of hydrochemical and hydrobiological regimes is discussed. It is shown that the prognoses of hydrobiological parameters on the base of hydrochemical data using regression analyses is not possible due to high variability of data. For the purpose of reconstruction hydrobiological data the complex indexes were worked, then the classification of lakes of Karelia was done. Using the methods of multivariate statistics and the contingency tables the connections between chemical and hydrobiological parameters were investigated. The prognoses tables were calculated to reconstruct the zooplankton and zoobenthos biomass on the base of total phosphorous concentration. The precision of the prognoses varied within 55-86%.